Changes in Rumen Bacterial Community Induced by the Dietary Physically Effective Neutral Detergent Fiber Levels in Goat Diets - Xue, Benchu; Wu, Mei; Yue, Shuangming; Hu, Anhai; Li, Xiang; Hong, Qionghua; Wang, Zhisheng; Wang, Lizhi; Peng, Quanhui; Xue, Bai (Frontiers in Microbiology, 2022)
Physically effective neutral detergent fiber (peNDF) is a concept that account for the particle length of NDF in a feed, sustaining the normal chewing behavior and rumen fermentation of ruminants. This study aimed to elucidate the effect of dietary peNDF on the growth performance and bacterial communities in the rumen of goats through high-throughput sequencing technique. A total of 30 male Lezhi black goats were randomly assigned to five groups, corresponding to 5 diets with identical composition and nutrient level but varied in forage lengths (the peNDF1.18 contents of the diets were 33.0%, 29.9%, 28.1%, 26.5%, and 24.8%, respectively). The whole trial lasted for 44d. As results shows, the feed intake and average daily gain (ADG) was the highest when peNDF1.18 content was 26.5%, in which the Papilla length of Dorsal sac in rumen was the highest. Chao1 and ACE indexes were similar among the treatments, while Shannon and Simpson indexes of the peNDF1.18=28.1% group were the highest (P < 0.05). As the level of dietary peNDF1.18 decreased, the dominant phylum transitioned from Bacteroidetes to Firmicutes. The top three dominant genera of rumen bacteria were Prevotella 1, Ruminococcaceae NK4A214 group, and Christensenella R-7 group. They all showed a quadratic correlation with dietary peNDF1.18 level (P < 0.05). The relative abundance of Ruminococcaceae UCG-011 was positively, while that of Prevotella 1 was negatively, correlated with Amino Acid Metabolism and Energy Metabolism (P < 0.01). In conclusion, dietary peNDF level influenced goat growth performance, rumen development, and rumen bacterial community structures, and a level of peNDF1.18 between 26.5 to 28.1% was considered optimal for goat diet.